2016
DOI: 10.1073/pnas.1609939113
|View full text |Cite
|
Sign up to set email alerts
|

Fluorine-19 NMR and computational quantification of isoflurane binding to the voltage-gated sodium channel NaChBac

Abstract: Voltage-gated sodium channels (Na V ) play an important role in general anesthesia. Electrophysiology measurements suggest that volatile anesthetics such as isoflurane inhibit Na V by stabilizing the inactivated state or altering the inactivation kinetics. Recent computational studies suggested the existence of multiple isoflurane binding sites in Na V , but experimental binding data are lacking. Here we use site-directed placement of 19 F probes in NMR experiments to quantify isoflurane binding to the bacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 25 publications
2
47
0
Order By: Relevance
“…To this end we considered a homology model of NaChBac based on the structural template of Na V Ab and subject to multi µs molecular dynamics simulations (90,91). Despite being a theoretical prediction, this structural model has been repeatedly experimentally validated (92,93). The superposition of NaChBac and Na V 1.4 reveals a structural match as good as the one observed for Na V Ms.…”
Section: Resultsmentioning
confidence: 99%
“…To this end we considered a homology model of NaChBac based on the structural template of Na V Ab and subject to multi µs molecular dynamics simulations (90,91). Despite being a theoretical prediction, this structural model has been repeatedly experimentally validated (92,93). The superposition of NaChBac and Na V 1.4 reveals a structural match as good as the one observed for Na V Ms.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, free energy perturbation based affinity calculations indicate that these binding sites are characterized by submillimolar dissociation constants, thus binding is likely to occur at physiological concentrations. Accordingly, in a combined computational and NMR investigation, two of these sites were unambiguously experimentally confirmed (Kinde et al, 2016). However, the lack of systematic in vivo mutagenesis studies does not allow us to draw strong conclusions on the relevance of these sites in mediating the drug induced condition of general anesthesia.…”
Section: Pore Domain Bindersmentioning
confidence: 94%
“…In a recent study of isoflurane binding to NaChBac using 19 F NMR, isoflurane was proposed to inhibit the channel through an interaction at the base of the selectivity filter and by impeding the pivoting motion at the S4–S5 linker and the hinge controlling gating and inactivation motions of S6 (Kinde et al 2016). A recent functional study of NaChBac employing electrophysiology and Markov modeling of NaChBac gating revealed that the effects of isoflurane on NaChBac could be described by increases in the rate constants for both channel activation and inactivation, with a dominant effect on inactivation (Sand et al 2017).…”
Section: Identification Of Anesthetic Binding Sites Within Prokaryotimentioning
confidence: 99%
“…Compared to the model of slow open-channel block, this model better described the empirical data, and suggests that isoflurane acts at two distinct binding sites to accelerate both activation and inactivation gating (Sand et al 2017). The isoflurane binding site at the base of the selectivity filter, identified by NMR (Kinde et al 2016), is likely responsible for facilitating inactivation.…”
Section: Identification Of Anesthetic Binding Sites Within Prokaryotimentioning
confidence: 99%